Quasi J-Regular Modules - AL – Shaiban , Rafid M.; AL-Mothafar, Nuhad S. (Iraqi Journal of Science, 2020)
Throughout this note, R is commutative ring with identity and M is a unitary R-module. In this paper, we introduce the concept of quasi J- submodules as a – and give some of its basic properties. Using this concept, we define the class of quasi J-regular modules, where an R-module J- module if every submodule of is quasi J-pure. Many results about this concept